The neutral interest rate: Past, present and future. A thematic review - Matteo Cacciatore; Bruno Feunou; G. Kemal Ozhan (Bank of Canada, 2024)
The decline in safe real interest rates over the past three decades has reignited discussions on the neutral real interest rate, known as R*. We review insights from the literature on R*, addressing its determinants and estimation methods, as well as the factors influencing its decline and its future trajectory. While there is a consensus that R* has declined, alternative estimation approaches can yield substantially different point estimates over time. The estimated neutral range is large and uncertain, especially in real-time and when comparing estimates based on macroeconomic data with those inferred from financial data. Evidence suggests that factors such as increased longevity, declining fertility rates and scarcity of safe assets, as well as income inequality, contribute to lowering R*. Existing evidence also suggests the COVID-19 pandemic did not substantially impact R*. Going forward, there is an upside risk that some pre-existing trends might weaken or reverse.
Keywords: E43; E52; E62; 330; Interest rates; Monetary policy; Monetary policy framework